Comparative Simulation Study of the Different Sources of Statistical Variability in Contemporary Floating-Gate Nonvolatile Memory - Roy, G.; Ghetti, A.; Benvenuti, A.; Erlebach, A.; Asenov, A. (IEEE transactions on electron devices, 2011)
For the first time, a comprehensive comparative study of the impact of different sources of statistical variability in nonvolatile memory (NVM) has been carried out using the 3-D numerical simulation of large statistical ensembles and approaches based on the impedance-field method. Results of the threshold voltage variability in a template 32-nm floating-gate NVM subject to random discrete dopants (RDD), line edge roughness, oxide thickness fluctuations, polysilicon granularity, and interface trapped charge (ITC) are presented. The relative impact of each source of statistical variability has been highlighted, with RDD being identified as the dominant source and ITC as the next most dominant source. Based on the simulation of statistical samples of 1000 microscopically different devices, the shape and spread of the statistical distribution associated with each individual and combined sources of variability have been found to significantly be different from a normal distribution, particularly within the tails that may have significant implications for design and yield. Finally, an ensemble of 59 000 devices is used to characterize the combined impact of all sources of variability.